Targeting Cancer Stem Cells by Genetically Engineered Chimeric Antigen Receptor T Cells - Alhabbab, Rowa Y. (Frontiers in Genetics, 2020)
The term cancer stem cell (CSC) starts 25 years ago with the evidence that CSC is a subpopulation of tumor cells that have renewal ability and can differentiate into several distinct linages. Therefore, CSCs play crucial role in the initiation and the maintenance of cancer. Moreover, it has been proposed throughout several studies that CSCs are behind the failure of the conventional chemo/radiotherapy as well as cancer recurrence due to their ability to resist the therapy and their ability to re-regenerate. Thus, the need for targeted therapy to eliminate CSCs is crucial, for that reason chimeric antigen receptor (CAR) T cells has currently been in use with high rate of success in leukemia and to some degree in patients with solid tumors. This review outlines the most common CSC populations and their common markers, in particular CD133, CD90, EpCAM, CD44, ALDH and EGFRVIII, the interaction between CSCs and the immune system, CAR T cell genetic engineering and signaling, CAR T cells in targeting CSCs and the barriers in using CAR T cells as immunotherapy to treat solid cancers.